PENGEMBANGAN LAYANAN JASA MELALUI INOVASI PADA PT. POS INDONESIA KOTA PEKANBARU - Muhammad Ali Hanafiah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
PT. Pos Indonesia is experiencing a lagging progress in services that have an impact on the community of service users. To overcome this, PT. Pos Indonesia Kota Pekanbaru developed a service before it, namely EMS (Express Mail Service) to be a service that was developed into an international shipping service, with a wider range. In addition to international shipping services, PT. Pos Indonesia also created its latest service innovation, the postshop development service that establishes partnerships with e-commerce companies and large outlets in Indonesia. The purpose of this research is to find out the development of services through selected and applied innovations and to find out what factors inhibit the development of services through innovation at PT. Pos Indonesia, Sudirman Street, Pekanbaru City. The theoretical concept used is a theory according to Evert M. Roggers with indicators of the dimensions of innovation that refer to five (5) elements in the dimensions of innovation, first Relative Adventage, Compability, Complexity, Triability, Observability. In this study using a qualitative approach using descriptive analysis methods. In collecting data, researchers used interview techniques, observation and documentation using purposive sampling technique as a source of information and data analysis. The results of this study indicate that, the development of services through innovation at PT. Pos Indonesia with its superiority and quality of services offered, does not necessarily escape its shortcomings. The development of this service innovation is quite well received, by providing several types of services according to the needs of the community. The latest innovation services implemented by PT. Pos Indonesia is international shipping and postshop construction. As well as the inhibiting factors are insufficient human resources, a limited budget, and lack of socialization with the community users of services at PT. Indonesian post.Keywords: Development, Service, Innovation